PENGARUH BIRO PERJALANAN WISATA SEBAGAI SALURAN DISTRIBUSI TERHADAP TINGKAT HUNIAN KAMAR PADA HOTEL ALL SEASONS LEGIAN BALI - Adi Yanti Putri, Ni Made; Sasrawan Mananda, I GPB; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2017)
The background of this study was based on of technology development that affect the online or offline room sales at All Seasons Legian Bali. Room sales are made through online travel agents is higher than the offline travel agents. It means the influence of offline travel agent is lower than the growth online travel agent. The purpose of this report is to determine the influence of travel agents as a distribution channel about rooms sales at All Seasons Legian Bali Hotel. The data were collected by observation, interviews, library research and documentations. Type of data were used in this research are qualitative and quantitative. The data sources were used are the primary and secondary data and the purposive sampling methods to determine the informant. The data were analyzed with the simple regression analysis techniques, simple correlation analysis, analysis of determination, t test with significant level of five percent. The data processing were using with SPSS (Statistical Package for Social Science) 16.00 for windows. Based on the calculation, The lowest room sales is 247 in the period of May 2009, while the highest room sales is 2.239 in the period of January 2012, and obtained a correlation is 3.9%, which means the relationship between the travel agent and level of room sales at All Seasons Legian is low. The suggestion could be given that the hotel should strengthen in relationship with travel agents, so that could to provide great contribution as a distribution channel in room sales at All Seasons Legian Hotel.
Keywords: Offline Travel Agent, Online Travel Agent, Room Occupancy